The development of sustainable tourism industry in Kilim, Langkawi - Zameli, Nurul Hikmah; Mohammad Afandi, Syamsul Herman; Samdin, Zaiton; Shuib, Ahmad; Che Ibrahim, Nur Syuhada (2013)
Sustainable tourism is a holistic approach to rural area such as Kilim, Langkawi. This paper discusses on the indicators of positive finding for tourism sectors in Kilim. The study focus on two indicators which are: sustaining tourism satisfaction and economic benefits of tourism. Research methods of this study are based on previous studies and information from tourism management in Kilim. Both indicators show positive feedbacks on tourism activities in Kilim. Local people attain benefits from tourism sector in many ways and this have increase their income and livelihood. The job opportunities also increase as there are economic activities related to tourism sector such as food production and transportation. Tourists also gain enjoyable experience as they are satisfied. The study can provide LADA, the managing agency some feedback on sustainable development for tourism in Kilim, Langkawi. In the mean time, Kilim can be developed into a successful sustainable tourist destination.